Fatigue crack growth prediction and analysis - Akyürek, Turgut. (Thesis (M.S.)- Bogazici University. Institute for Graduate Studies in Science and Engineering, 1984., 1984)
In this thesis, A computer program predicting the fatigue life of the specimens subjected to randomized black loading is prepared. A detailed description of fatigue crack growth and predictive models are reviewed. The computer program AKYUREK-I takes also the retardation phenomenon into consideration. The Wheeler and Willenborg retardation models are used. In the program, center-crack panel, single and double edge cracked specimens, compact tension specimen, bend specimen and surface flawed plates are considered. A cycle-by-cycle integration scheme is used. The results of some experiments,are used to review the existing crack growth prediction models.
Keywords: Materials -- Fatigue.; Fracture mechanics.